Development of Inorganic Molecular Shape Model Using 3D Printer to Strengthen Student's Conceptual Understanding - Rizal Galih Pratama; Johnsen Harta (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This research aims to develop a product in the form of an inorganic molecular shape model using a 3D printer, analyze the validity, practicality, effectiveness of the product, and strengthen students' conceptual understanding using the product. The method is Research and Development (R&D) based on the Analysis, Design, Development, Implementation and Evaluation (ADDIE) model. The supporting instruments for this research are product and instrument validation sheets, product readability questionnaires, pretest-posttest questions, question during the trial, observation sheets for students' conceptual understanding, and student response questionnaire to the product. The results showed that the product developed was following the ADDIE model because the five stages were carried out systematically; the product being developed has very high validity with an average percentage of 96.88%; the average percentage of practicality is 95.17% which is categorized as very practical, and the average percentage of effectiveness is 94.69% which is categorized as very effective; the product developed can strengthen students' conceptual understanding shown on the average percentage of conceptual understanding indicators achievement during the trial was 90.61% and the observation result was 94.69%, both of which belong to very high category. There was an increase in the average pretest value of 33.93 and post-test of 63.99. The results of the Rasch analysis after using this product showed that the consistency of students' answers was 0.71 (quite good), the quality of the items was 0.93 (very good), and the interaction between the consistency of students' answers was 0.68 (quite good). The product can be used to strengthen students' conceptual understanding on the topic of molecular shape.